Perceptions of operating room staff of their job demands and turnover intentions in Western Cape Metropolitan provincial hospitals - Kunz, Thalita Yvonne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MNur)--Stellenbosch University, 2022.